Does the impact of osteoarthritis vary by age, gender and social deprivation? A community study using the International Classification of Functioning, Disability and Health. (August 2014) - Pollard, Beth; Dixon, Diane; Johnston, Marie
Abstract Purpose: The aim of the study was to explore if the impact of osteoarthritis varies with respect to age, gender and social deprivation. Impact was defined as impairment, activity limitations and participation restriction (International Classification of Functioning, Disability and Health (ICF)). Investigating the functioning of the ICF model for subgroups is important both practically and theoretically. Method: The sample comprised a community sample of 763 people diagnosed with osteoarthritis. Uncontaminated measures of the ICF constructs were developed using discriminant content validity from a pool of 134 items, including the WOMAC and SF-36. Multigroup Structural Equation Modelling was used to explore if the same pathways exist for subgroups of gender, age and social deprivation. Results: Different significant paths were found for gender and social deprivation: impairment did not predict participation restriction for women and those most deprived, whereas these paths were significant for men and those less deprived. No difference in the paths was found for age. Conclusions: The impact of osteoarthritis appears to vary with respect to gender and social deprivation but not age. This suggests both that osteoarthritis per se does not adequately explain the health outcomes observed and that different clinical approaches may be appropriate for people of different gender and levels of deprivation. Implications of Rehabilitation The ICF model appears to vary with respect to gender and social deprivation for people with osteoarthritis. The ICF model did not appear to vary with respect to age for people with osteoarthritis. Different treatments and interventions for osteoarthritis may need to be targeted for specific gender and social deprivation groups.